LEGAL PROTECTION OF FAMOUS TRADEMARKS AGAINST COUNTERFEIT DANIEL WELLINGTON AND LONGCHAMP BRANDS ON E-COMMERCE - Princess Danaarta Cahya Santoso (Widya Gama Intellectual Property Rights, 2026)
A trademark is a form of intellectual property. As a work of human thought, it deserves to be appreciated and its rights protected. Trademark rights are limited to the use of products that are sold and have economic value, as trademark rights are exclusive rights granted by the state to the owner of a registered trademark. for a certain period of time by using the brand yourself or giving permission to another party to use it. Protection law for holder legitimate brand​ aim give right exclusive to owner brand so as not to There is other parties who may use similar signs​ or identical For the same product or almost similar. Exclusive rights This nature monopoly, which means only holder entitled brand​ use it. The owner brand own freedom For utilise the brand throughout comply applicable regulations, as well as own right For prohibit others from using the brand or give permission use. Research This discuss two main points problem namely First , What are the forms of trademark violations in E-Commerce against the famous brands Daniel Wellington and Longchamp?; Second, How is the protection of famous brands in E-Commerce according to Law Number 20 of 2016 regarding the existence of Counterfeit Brands of Famous Brands? methods used​ in study This is juridical normative with approach legislation , theory law , document law , approach cases and approaches conceptual . Research results This conclude that First, there is form violation trademark rights in e-commerce against well-known brands like Daniel Wellington and Longchamp. Second, protection law against famous brands in e-commerce based on Law No.20 of 2016 is related with the presence of fake brands from famous brands